Interaction between State Law and Religious Law: Husband's Authority in Muslim Family Law in Indonesia - Wahyu Saputra; Indah Permata (Indonesian Journal of Islamic Law, 2022)
This research explores the interaction between state law and religious law in regulating husbands' authority in Muslim families in Indonesia. Using a qualitative approach with document analysis methods, in-depth interviews, and case studies, this research identifies how the Compilation of Islamic Law (KHI) and Marriage Law No. 1 of 1974 plays a role in shaping power dynamics in the family. The findings show that despite efforts to harmonize traditional principles of Islamic law and more inclusive modern legal standards, implementation still faces various challenges, including cultural resistance, lack of legal awareness, and inconsistencies in law enforcement. Additionally, international influence and women's human rights activism play an important role in pushing for fairer and more equal legal reforms. Case studies from various regions in Indonesia show variations in legal application that reflect the influence of local context on the interpretation and implementation of family law. The results of this research highlight the need for a holistic approach that includes legal education, ongoing advocacy, and strengthening the capacity of legal institutions to achieve greater gender equality in Muslim family law in Indonesia.